Analisis Pokok Persoalan Hukum Pidana Formal (Hukum Acara Pidana) Perspektif Kontemporer Dengan Mempertimbangkan Kuhp Baru Dalam Persoalan Di Era Digital - Marsela Gusnefa; Hejri Lidiatri Usman; Sohpi Gustinia; Sonia Ivana Barus (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Significant changes in the New Criminal Code (Law No. 1 of 2023) and the development of the Digital Era pose new challenges in the implementation of the criminal procedure law (KUHAP), especially in the harmonization between the needs of society as a whole and the protection of the personal rights of every citizen and the use of Electronic Evidence. This research aims to analyze and describe the implications of the new Criminal Code on criminal procedural law in the context of formal criminal law enforcement, as well as identify the main problems and challenges that arise in the digital era, especially related to the recognition and use of electronic evidence. The method used is qualitative legal research with a normative approach. The results of the study show that the new Criminal Code expands the subject of criminal law and the sanction system which has an impact on the adaptation of the procedures of the Criminal Code. The digital age demands more explicit regulation regarding electronic evidence to address the challenges of cybercrime. Criminal procedure law must continue to innovate in order to remain able to balance the public interest and individual rights fairly and effectively in the contemporary context. This research seeks to provide a more comprehensive perspective based on significant criminal law developments including law reform and enforcement.